Performance Appraisal among Civil Servants through Electronic Performance (E-Performance) at Badan Kepegawaian Daerah (BKD) of Karo Regency, North Sumatera Province (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
This study examined the implementation of electronic performance (e-performance) appraisal for Civil Servants, and identified the obstacles and efforts made. A qualitative descriptive method with an inductive approach was used, while the data were collected through observation, documentation, and interviews. The data were then analyzed through several steps; data reduction, data display, and inference. Findings indicate that the performance assessments of Civil Servants through e-performance are satisfactory and comply with the Standard Operating Procedures outlined in Regent Regulation Number 36 of 2017. However, improvement in terms of service quality and accountability can be promoted. The obstacles encountered in evaluating performance through e-performance include inadequate infrastructure, employees' resistance to mindset change, and the absence of a connection between e-performance and employee work goals (SKP). Efforts have been made to address these challenges, such as adding necessary infrastructure and organizing socialization sessions on e-performance operation. The author advises conducting training specifically related to e-performance operations and refining the e-performance program to integrate it with employee work goals (SKP).ABSTRAKTujuan penelitian ini untuk mengetahui pelaksanaan penilaian kinerja Aparatur Sipil Negara (ASN) menggunakan electronic performance (e-performance), hambatan serta upaya yang dilakukan. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan induktif. Dalam memperoleh data menggunakan cara observasi, dokumentasi, dan wawancara. Sedangkan untuk analisis data yang menggunakan reduksi data, tampilan data, dan inferensi. Adapun hasil penelitian menunjukkan penilaian kinerja ASN melalui electronic performance (e-performance) yang sudah cukup baik dan sudah berjalan sesuai Standart Operasional Prosedur berdasarkan Peraturan Bupati Nomor 36 Tahun 2017, namun perlu ditingkatkan dalam aspek kualitas pelayanan dan akuntabilitas. Hambatan dalam penilaian kinerja melalui e-performance adalah kurangnya sarana prasarana, pegawai belum mengubah pola pikir dan e-performance belum tersambung dengan sasaran kerja pegawai (SKP). Upaya yang dilakukan menambah sarana prasarana yang dibutuhkan, mengadakan sosialisasi cara pengoperasian e-performance. Saran yang diberikan sebaiknya mengadakan pelatihan terkait operasional e-performance dan menyempurnakan program e-performance yang terintegrasi dengan sasaran kerja pegawai (SKP).